Effect of relative humidity on sporulation and germination of spores of Cercospora and Pseudocercospora spp. infecting legumes - K.V. MALLAIAH, M. RAGHU RAM and (Indian Phytopathology, 2002)
The pattern of conidial germination and sporulation at different RH levels in 4 Cercospora spp. and 6 Pseudocercospora spp. causing foliar diseases on Fabaceae hosts were investigated. Opt. sporulation occurred at 100% RH.